Effect of Smokeless Tobacco on the Outcome of Swiss Albino Mice Pregnancy & Changes in their Offspring’s Body Weight; An Experimental Study (Medical Forum Monthly, 2024)
Objective: To study the harmful effects of smokeless chewing local tobacco on Swiss Albino mice pregnancy outcome and observe the effect on their offspring’s body weight.Study Design: An Experimental studyPlace and Duration of Study: This study was conducted at Anatomy Department Al- Tibri Medical College, Isra University Karachi during June 2015 to December 2015.Materials and Methods: Twenty pregnant Swiss albino mice and their 40 offspring male and female equal number, Selected randomly. The mice were divided into Experimental and control groups. Inclusion criteria were the healthy offspring of two weeks age. At the time of birth initial weight was taken and the final weight was taken after two weeks. Exclusion criteria was unhealthy, less or more than two week’s age. Independent sample t-test was used for analysis of data through SPSS version 20.0.Results: Total of 20 female Swiss albino mice divided equally into two groups experimental and control. Experimental group was kept on 5% smokeless tobacco. Twenty offspring from experimental and twenty offspring from control group of both sexes were taken. Initial and final weights of both groups were recorded. Significant difference was observed in initial and final weights of offspring with P-value=0.01.Conclusion: Tobacco which is frequently used in our region without any knowledge of its harmful effects. It is proved that smokeless tobacco not only reduces the weight of offspring but during pregnancy it effects the growing fetus leading to stillbirth and neonatal deaths.